The Role of Notaries in Copyright Legal Counseling (Case Study: Riot Games Vs Moonton) - Indriani Magdalen Halim (Jurnal Indonesia Sosial Sains, 2025)
This study examines the role of notaries in providing legal counseling related to copyright transfer. The position of a notary as a public official directly involves serving the interests of the public by offering services such as legal counseling, as regulated by Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 on the Notary Profession. Specifically, in the context of copyrights, notaries must ensure that the copyright status is valid and duly held by the appearing party. The objective of this study is to clarify the authority of notaries in providing legal counseling related to copyright through the case study of Riot Games vs. Moonton, and to understand how notaries perform their role in facilitating copyright transfers through authentic deeds. The research method used is a normative-empirical legal research method, which utilizes secondary data as the primary material, consisting of primary, secondary, and tertiary legal sources. Secondary data obtained through literature study is complemented and strengthened by primary data in the form of interviews. The results of the study indicate that legal counseling by notaries is essential to ensure that parties understand their rights and obligations before carrying out specific legal acts. Authentic deeds prepared by notaries can provide legal certainty and protection for the parties involved, thereby helping to prevent disputes. Notaries play a vital role in ensuring that the transfer of rights is conducted legally and in accordance with the applicable law.